Tata Kelola Wisata Hutan Mangrove di Desa Ogomolos Kecamatan Mepanga, Kabupaten Parigi Moutong - Anggi Apriliani; Muhammad Nawawi; Irwansyah Kamindang (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Environmental-based tourism development has become an important strategy for promoting local economic growth while ensuring the sustainability of coastal ecosystems. One form of environmentally based tourism with considerable potential is mangrove forest tourism. This study aims to analyze the governance of mangrove forest tourism in Ogomolos Village, Mepanga District, Parigi Moutong Regency. This study employs a qualitative-descriptive approach to provide an in-depth understanding of mangrove tourism governance. Data were collected through observation, interviews, and documentation. The analysis is based on the Destination Management Organization (DMO) framework proposed by Sheehan & Ritchie (2005), which includes the aspects of coordination of tourism stakeholders, destination crisis management, and destination marketing. The results indicate that the management of mangrove forest tourism in Ogomolos Village involves collaboration between the village government and the Tourism Awareness Group (Pokdarwis). The village government plays a role in policy formulation and budget support, while Pokdarwis is responsible for the operational management of the tourism area, maintaining environmental sustainability, and supporting tourism activities. However, the governance of the tourism destination has not yet been optimal. This is due to weak coordination among stakeholders that has not been formally institutionalized, the absence of an adequate destination crisis management system, and limited destination marketing strategies that have not yet fully utilized digital media.